2013
DOI: 10.3928/00989134-20130226-01
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Computer Application for Promoting Physical Activity

Abstract: Despite evidence that physical activity reduces the risk of falls and other causes of disability and death, the majority of older adults do not engage in physical activity on a regular basis. Mobile technology applications have emerged as potential resources for promoting physical activity behavior. This article describes features of a new application, Ready~Steady, highlighting approaches used in its design and development, and implications for clinical practice. Iterative processes enabled the design, develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…Metaphors or avatars are commonly used to represent the monitored activity to the user. The use of metaphors and avatars is common and reasonable in game design, but also in persuasive design: showing physical activity levels as, for example, a flower, 43 a garden, 44,45 or art. 46 Such metaphorical displays are in general well accepted and positively received.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metaphors or avatars are commonly used to represent the monitored activity to the user. The use of metaphors and avatars is common and reasonable in game design, but also in persuasive design: showing physical activity levels as, for example, a flower, 43 a garden, 44,45 or art. 46 Such metaphorical displays are in general well accepted and positively received.…”
Section: Discussionmentioning
confidence: 99%
“…46 Such metaphorical displays are in general well accepted and positively received. [43][44][45][46][47] Lin et al 27 specifically showed that exhibiting activity through the growth and emotional state of virtual fish indeed increased users' awareness of their levels of physical activity and increased their motivation to exercise. As abstract presentations of activity (e.g., by a graph) have shown a decreasing adherence after a few weeks of use, 12 such metaphors seem a promising tool for motivation in mobile gaming applications.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 2 trial or outcome studies, five articles focused on software design and evaluation and the remaining articles are on focus groups and interview studies on stakeholders' opinions on smart phone apps for physical activity (see Table 1). [25] × × [26] × [27] × × × × × × × × × [28] × × × × × × × × [29] × × × × [30] × × × [31] × [32] × × × × × × × × × × × × [33] × × [34] × × × × × × × [35] × × × × [36] × × × × × × [37] × [38] × × × [39] × × × × × [40] × [41] × [42] × × × × [43] × × [44] Illustrations in figure 2 and table 2 show features that are highly present in articles on physical activity intervention studies, those features that were occasionally mentioned, or those that were not cited often in these articles. Visualisation of persuasive features is presented to provide more insights about the highlights, 9 gaps and blank spots [45] in current mobile application persuasive design features on physical activity.…”
Section: Data Extractionmentioning
confidence: 99%
“…Applications used visually pleasing display features that allowed user feedback to be not only liked by the user, but also to convey complex information in a pleasurable way [33]. Metaphorical representations were commonly used to display the user's physical activity in a way that was intuitively understood by the user [34] [37].…”
Section: Dialogue Supportmentioning
confidence: 99%
See 1 more Smart Citation